The FORA Fog Computing Platform for Industrial IoT. Issue 98 (May 2021) - Pop, Paul; Zarrin, Bahram; Barzegaran, Mohammadreza; Schulte, Stefan; Punnekkat, Sasikumar; Ruh, Jan; Steiner, Wilfried
Abstract: Industry 4.0 will only become a reality through the convergence of Operational and Information Technologies (OT & IT), which use different computation and communication technologies. Cloud Computing cannot be used for OT involving industrial applications, since it cannot guarantee stringent non-functional requirements, e.g., dependability, trustworthiness and timeliness. Instead, a new computing paradigm, called Fog Computing, is envisioned as an architectural means to realize the IT/OT convergence. In this paper we propose a Fog Computing Platform (FCP) reference architecture targeting Industrial IoT applications. The FCP is based on: deterministic virtualization that reduces the effort required for safety and security assurance; middleware for supporting both critical control and dynamic Fog applications; deterministic networking and interoperability, using open standards such as IEEE 802.1 Time-Sensitive Networking (TSN) and OPC Unified Architecture (OPC UA); mechanisms for resource management and orchestration; and services for security, fault tolerance and distributed machine learning. We propose a methodology for the definition and the evaluation of the reference architecture. We use the Architecture Analysis Design Language (AADL) to model the FCP reference architecture, and a set of industrial use cases to evaluate its suitability for the Industrial IoT area. Highlights: Fog Computing is envisioned as a new paradigm to implement Industrial IoT solutions. The Fog Platform relies on hypervisors to host mixed-criticality applications. The Architecture Analysis Design Language (AADL) was used to model the architecture. Industrial use cases were used to help define and the evaluate the Fog Platform.